Design of multiple near-orthogonal spectrally-compliant waveforms via alternating successive convex approximations and projections - Alison Cheeseman; Raviraj S. Adve (IET Radar, Sonar & Navigation, 2019)
The authors consider the design of multiple near-orthogonal transmit waveforms for a high-frequency surface wave radar (HFSWR) system operating in a congested spectral environment where the radar must adhere to strict regulations on the interference it can cause to on-going communication links. The HFSWR application necessitates multiple waveforms to increase the overall unambiguous radar range. Ideally, the waveforms would be constant amplitude, have low autocorrelation sidelobes, and low pulse-to-pulse cross-correlations, all while meeting the imposed spectral constraints; however, it is impossible to know a priori that such waveforms exist. They propose an algorithm based on alternating successive convex approximations and projections to design waveforms with low pulse-to-pulse cross-correlation which meet strict spectral and autocorrelation sidelobe constraints while minimising the amplitude modulation. In the simulation, the proposed algorithm is found to converge rapidly and when compared to similar methods from the recent literature, the proposed algorithm is found to generate waveforms with significantly lower peak-to-average power ratios and better pulse compression properties.